2020
DOI: 10.1002/cyto.b.21955
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of the ClearLLab 10C B cell tube

Abstract: Introduction: Pre-analytical and analytical errors can threaten the reliability of flow cytometry (FC) results. A potential solution to some of these is the use of dry, premixed antibodies, such as the ClearLLab 10C system. The purpose of the present study was to compare the diagnostic performance of the ClearLLab 10C B cell tube with that of our standard laboratory practice.Methods: We compared the diagnoses made with the ClearLLab 10C B cell tube (experimental strategy) with those made with standard laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The captured and amplified DNA was sequenced using NextSeq550 platform (Illumina ® ). The results were analyzed using DataGenomics platform as described elsewhere [37][38][39].…”
Section: Targeted Next Generation Sequencing (Ngseq)mentioning
confidence: 99%
“…The captured and amplified DNA was sequenced using NextSeq550 platform (Illumina ® ). The results were analyzed using DataGenomics platform as described elsewhere [37][38][39].…”
Section: Targeted Next Generation Sequencing (Ngseq)mentioning
confidence: 99%
“…Other multicolor antibody panels described and evaluated in this issue are a 10-color screening panel for B-cell neoplasia (Espasa et al, 2021) that includes CD200 (Sorigue et al, 2020), and a 10-color panel for MRD assessment in T-lymphoblastic leukemia (Tembhare et al, 2021). The former panel (Espasa et al, 2021), which makes use of dry reagents, has also been evaluated in a multicenter study recently reported in the journal (Hedley et al, 2021).…”
mentioning
confidence: 99%
“…Gupta and colleagues, also in this issue (Gupta et al, 2021), illustrate the use of another multiparametric data visualization method, the radar plot (Jafari et al, 2018; Violidaki et al, 2020), to facilitate distinction between acute promyelocytic leukemia with PML‐RARA and AML with NPM1 mutation, whose phenotypes may overlap (Zhou et al, 2019). Other multicolor antibody panels described and evaluated in this issue are a 10‐color screening panel for B‐cell neoplasia (Espasa et al, 2021) that includes CD200 (Sorigue et al, 2020), and a 10‐color panel for MRD assessment in T‐lymphoblastic leukemia (Tembhare et al, 2021). The former panel (Espasa et al, 2021), which makes use of dry reagents, has also been evaluated in a multicenter study recently reported in the journal (Hedley et al, 2021).…”
mentioning
confidence: 99%